The Use of Kinesthetic Perception in Music Education at Primary School - Kepule, Iveta (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
The article looks at the opportunities to use kinesthetic perception in music teaching taking as a basis H.Gardner’s theory of intellectual abilities and in connection with methodological approaches of E.J.Dalcroze, Z.Kodaly, C.Orff to music teaching. The variants of music language, music perception and creative activity which are offered in the article facilitate a simpler and more dynamic mastery of the taught music content, which in its turn creates positive conditions for students’ self-realization in music teaching. The compulsory content of music education is examined in connection with the „Regulations on the state standard of basic education and standards in subjects” in music.